An expert trajectory design for control of nuclear research reactors - (:unkn) unknown (PERGAMON-ELSEVIER SCIENCE LTD, 2009)
In this study, an expert trajectory was proposed for control of nuclear research reactors. The trajectory being followed by the reactor power is composed of three parts. In order to calculate periods at the midpoint of each part of the trajectory, a period generator was designed based on artificial neural networks. The contribution of the expert trajectory to the reactor control system was investigated. Furthermore, the behavior of the controller with the expert trajectory was tested for various initial and desired power levels, as well as under disturbance. It was seen that the controller could control the system successfully under all conditions within the acceptable error tolerance. (c) 2009 Elsevier Ltd. All rights reserved.
Keywords: Nuclear reactor control; Neural networks; Trajectory planning; FUZZY-LOGIC